Six-year follow-up of slaughterhouse surveillance (2008-2013): the Catalan Slaughterhouse Support Network (SESC) - Vidal, E.; Tolosa, E.; Espinar, S.; Pérez de Va, B.; Nofrarías, M.; Alba, A.; Allepuz, A.; Grau-Roma, Llorenc; López-Soria, S; Martínez, J.; Abarca, M.L.; Castellà, J.; et al. (SAGE, 2016)
Meat inspection has the ultimate objective of declaring the meat and offal obtained from carcasses of slaughtered animals fit or unfit for human consumption. This safeguards the health of consumers by ensuring that the food coming from these establishments poses no risk to public health. Concomitantly, it contributes to animal disease surveillance. The Catalan Public Health Protection Agency (Generalitat de Catalunya) identified the need to provide its meat inspectors with a support structure to improve diagnostic capacity: the Slaughterhouse Support Network (SESC). The main goal of the SESC was to offer continuing education to meat inspectors to improve the diagnostic capacity for lesions observed in slaughterhouses. With this aim, a web-based application was designed that allowed meat inspectors to submit their inquiries, images of the lesions, and samples for laboratory analysis. This commentary reviews the cases from the first 6 years of SESC operation (2008–2013). The program not only provides continuing education to inspectors but also contributes to the collection of useful information on animal health and welfare. Therefore, SESC complements animal disease surveillance programs, such as those for tuberculosis, bovine cysticercosis, and porcine trichinellosis, and is a powerful tool for early detection of emerging animal diseases and zoonoses.